2021
DOI: 10.3390/nu13124282
|View full text |Cite
|
Sign up to set email alerts
|

Shatavari Supplementation in Postmenopausal Women Improves Handgrip Strength and Increases Vastus lateralis Myosin Regulatory Light Chain Phosphorylation but Does Not Alter Markers of Bone Turnover

Abstract: Shatavari has long been used as an Ayurvedic herb for women’s health, but empirical evidence for its effectiveness has been lacking. Shatavari contains phytoestrogenic compounds that bind to the estradiol receptor. Postmenopausal estradiol deficiency contributes to sarcopenia and osteoporosis. In a randomised double-blind trial, 20 postmenopausal women (68.5 ± 6 years) ingested either placebo (N = 10) or shatavari (N = 10; 1000 mg/d, equivalent to 26,500 mg/d fresh weight shatavari) for 6 weeks. Handgrip and k… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
0
10
0
3
Order By: Relevance
“…Recently, evidence has emerged that shatavari supplementation may increase skeletal muscle strength. We showed that 6 weeks of shatavari supplementation signi cantly improved handgrip strength in postmenopausal women [1]. Further, myosin regulatory light chain phosphorylation, which is a known marker of improved myosin contractile function, was increased in the vastus lateralis following shatavari supplementation.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Recently, evidence has emerged that shatavari supplementation may increase skeletal muscle strength. We showed that 6 weeks of shatavari supplementation signi cantly improved handgrip strength in postmenopausal women [1]. Further, myosin regulatory light chain phosphorylation, which is a known marker of improved myosin contractile function, was increased in the vastus lateralis following shatavari supplementation.…”
Section: Introductionmentioning
confidence: 78%
“…Estradiol receptor activation by phytoestrogens could improve muscle strength, particularly in the estradiol de cient postmenopausal population that we studied previously. Indeed, this was the rationale for our original work [1]. Estradiol is known to improve myosin binding function and muscle force production [3].…”
Section: Introductionmentioning
confidence: 96%
“…최종 선정된 연구 45편 중 10편의 임상 연구에 포함된 한의학적 중재를 살펴보면 4편 [15][16][17][18] 은 한약에 대한 연구 였으며 이 중 3편은 추출물, 1편은 탕약이었다. 그 다음 으로 도인운동을 다룬 연구가 3편 [19][20][21] , 전침을 포함한 침술이 1건 22) 이었으며 한의복합치료는 2건 23,24) 이었다.…”
Section: 한의 치료 중재unclassified
“…한약의 경우, 한국 겨우살이(Korean mistletoe) 추출물, 10편의 임상 연구 중 8편 [17][18][19][20][21][22][23][24] 에서 악력(handgrip strength)…”
Section: 한의 치료 중재unclassified
“…Shatavari, also known as Asparagus racemosus Willd, is an ancient ayurvedic herb with phytoestrogenic effects. It maintains muscle (ergogenic) and bone health in postmenopausal women [36] .…”
Section: Nutraceuticals For Menopausal Symptomsmentioning
confidence: 99%